Application of The Principle of Good Faith In Selling Disputes of Selling Buying Using Pre Project Selling - Moh. Saleh; Rochmad Bayu Setyo Waluyo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
Selling and buying land is a legal act that gives birth to rights and obligations for sellers and buyers. In carrying out the sale and purchase of land, it is mandatory to be guided by the legal provisions regarding the legal procedures to be followed, and must prioritize the principle of good faith in the bargaining stage up to the payment and sale and purchase agreement. In practice, lawsuits are often found on the attitude of one party that does not reflect the principle of good faith in buying and selling, of course this is against the rule of law and can be detrimental to other parties. This research is expected to be a means for legal scholars to understand the context of the land sale and purchase agreement. This research method used a normative juridical method with a conceptual approach, legislation and a case approach. The conclusion of this study is that in making an agreement, it is necessary to pay attention to fulfilling the elements of Article 1230 BW in the form of a valid condition of an agreement, as well as prioritizing the principle of good faith as the basis for making a land sale and purchase agreement, it should be done before the PPAT, if the land has not been certified, it can be done before the village head. . The process of buying and selling land in accordance with procedures and without any elements of forgery will reduce the level of legal risk in the future, besides the benefits of using the principle of good faith for the buyer, namely the rights of the buyer which are protected by law.